The characterization of a novel abscission-related gene in Arabidopsis thaliana - Liu, Yang (2012)
Abscission is an important process in the life cycle of a plant. It takes place in predetermined sites called Abscission Zones (AZs). In the previous study of our group, a potential abscission-related gene At1g64405 (G2) was identified of particular interest using a transcriptional analysis. The aim of this study was to characterize this gene in detail.